2017
DOI: 10.1016/j.jsps.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Volatile constituents and biological activities of the leaf and root of Echinacea species from South Africa

Abstract: is used ethnomedicinally for the treatment of various diseases such as cough, respiratory infections, and bronchitis among other uses in Eastern Cape region of South Africa. This study evaluated the volatile components of the essential oil of the plant, its toxicity, anti-inflammatory and analgesic activities in rodents. Dried leaf and root of the plant were separately processed by hydrodistillation for 4 h and their essential oils (EOs) were collected. Extracted oils were subjected to GC/GC-MS analysis. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Echinacea purpurea, also known popularly as echinacea, is a species originally from the United States and has been used for centuries by Native Americans for combating various diseases [48]. This species appears in the list of monographs of traditional phytotherapy use of the European Medicines Agency (EMA), and it is in the MFFB for internal use to combat cold symptoms.…”
Section: Echinacea Purpureamentioning
confidence: 99%
See 1 more Smart Citation
“…Echinacea purpurea, also known popularly as echinacea, is a species originally from the United States and has been used for centuries by Native Americans for combating various diseases [48]. This species appears in the list of monographs of traditional phytotherapy use of the European Medicines Agency (EMA), and it is in the MFFB for internal use to combat cold symptoms.…”
Section: Echinacea Purpureamentioning
confidence: 99%
“…Nyalambisa et al [48] demonstrated the anti-inflammatory activity of the essential oil of its roots by the reduction of paw edema in mice. They also elucidated its chemical composition as mainly germacrene D, naphthalene, caryophyllene oxide, α-phellandrene (7), and α-cadinol (8).…”
Section: Echinacea Purpureamentioning
confidence: 99%
“…For example, different parts of E. purpurea plants were hydrodistillated and tested for their anti‐inflammatory and analgesic activities. The main components found in the leaf and root EOs included germacrene D (18.1% and 20.3%, respectively), naphthalene (7.8% and 6.4%, respectively), caryophyllene oxide (11.3% and 12.2%, respectively), α‐phellandrene (6.9% and 6.6%, respectively), α‐cadinol (9.1% and 5.9%, respectively), and caryophyllene (4.5% and 4%, respectively, Nyalambisa et al, ). Another study reported by Mazza and Cottrell () showed that the major compound found in E. purpurea root EO was α‐phellandrene, whereas, in flower, leaf, and stem tissues, it was β‐myrcene.…”
Section: Chemical Composition Of Essential Oils Obtained From Echinacmentioning
confidence: 99%
“…Our attention is focused on the extraction of bioactive compounds from Echinacea angustifolia , a native plant in both North America and Europe. This species has a long history of medical use for a variety of conditions especially for its immunostimulant effects, in the prevention and treatment of upper respiratory tract infections …”
Section: Introductionmentioning
confidence: 99%
“…This species has a long history of medical use for a variety of conditions especially for its immunostimulant effects, in the prevention and treatment of upper respiratory tract infections. 7 Echinacea angustifolia metabolome profile is well documented 3 and several groups of constituents including alkamides, polysaccharides and caffeic acid derivatives are considered important for its biological activity. 8 The objective of the present study was the optimisation of different green extractive methods to obtain the highest yield of bioactive compounds that could be used as improved source for therapeutic applications, especially polysaccharides and antioxidants, the most important bioactive compounds recognised for their immunostimulant activity.…”
Section: Introductionmentioning
confidence: 99%